Investigation of the Wear Resistance of a Journal Bearing with Polymer-Coated Grooved Support Ring - V. V. Vasilenko; V. I. Kirishchieva; M. A. Mukutadze; V. E. Shvedova (Advanced Engineering Research, 2023)
Introduction. In modern heavy-loaded friction units, metallopolymer coated bearings operating in the boundary friction mode are widely used. Their successful application is provided by the viscoelastic deformation of these coatings under load. To pass from boundary friction to liquid friction, it is required to create a bearing hydrodynamic wedge. Currently, the use of journal bearings with polymer-coated grooved support ring is hindered by the lack of a methodology for their calculation. This work analyzes a model of movement of a micropolar lubricant in the operating clearance of a journalbearing with a nonstandard support profile having a PTFE composite coating with a groove on the bearing surface.   The study aims at establishing the dependence of the stable hydrodynamic regime on the width of the groove on the surface of the bearing profile.   Materials and Methods. Tribological tests of journal bearings with a nonstandard bearing profile having a polymer coating with a groove on the surface were carried out on samples in the form of partial bushes (blocks). Using the equation of movement of a lubricant with micropolar rheological properties, as well as the continuity equation, new mathematical models were obtained that took into account the width of the groove, polymer coating, and nonstandard bearing profile.   Results. A significant expansion of the applicability of design models of journal bearings with structural changes has been achieved. Polymer-coated bearings with a groove provided a hydrodynamic lubrication mode. The results obtained allowed us to evaluate the operational characteristics of the bearing: hydrodynamic pressure value, load capacity, and coefficient of friction.   Discussion and Conclusions. The design of polymer coated journal bearing and a groove 3 mm wide on the surface of the liner provided a stable ascent of the shaft on the hydrodynamic wedge, which was validated experimentally. The experiments were carried out for journal bearings with a diameter of 40 mm with a groove 1–8 mm wide, at a sliding speed of 0.3–3 m/s and a load of 4.8–24 MPa.